Teknik Pembenihan dan Analisa Usaha Ikan Corydoras Panda (Ostariophysi: Siluriformes: Callichthyidae) di PT Qianhu Joe Aquatic Bogor, Jawa Barat - Muhammad Ikhwan Ihtifazhuddin; Dimas Galang Prakosa; Herma Setyowati; Lusiana BR Ritonga (Faculty of Science and Technology University Ibrahimy, 2026)
Panda Corydoras fish (Ostariophysi: Siluriformes: Callichthyidae) is a type of freshwater ornamental fish that is popular among aquarium hobbyists. This fish has a high aesthetic appeal, so it is widely sought after as an aquarium ornamental fish. This study aims to explore the Corydoras Panda fish breeding technique applied at PT Qianhu Joe Aquatic, as well as to conduct a business analysis to determine how profitable and sustainable this cultivation activity is. The results of the study indicate that the breeding technique applied at PT Qianhu Joe Aquatic is quite effective, with a FR of 71% and SR of 76%. From an economic perspective, this business shows good profit potential with a B/C ratio of 1.39 and a Payback Period of around 5 months and 26 days. Thus, the cultivation of Panda Corydoras fish at PT Qianhu Joe Aquatic is a profitable and sustainable business, with opportunities for further development in both domestic and international markets.